Partisipasi Perempuan dalam Ranah Politik Lokal: Kajian Sosial Politik di Klaten Jawa Tengah - Ririh Megah Safitri (IAIN Salatiga, 2019)
Women's participation in the political sphere is a response from government policies related to 30%. women's quota. The dynastic political label attached to political activities in Klaten became an element of influence over the survival strategy undertaken by women cadres. This research uses descriptive qualitative method. The purpose of this study is to explain the participation of women political cadres related to representation, relations and power in the local political sphere. The results of the study showed that conditions that did not prioritize women were not created in political activities due to socio-cultural factors and stereotypes inherent in women, but the local political sphere was able to become a space for female political cadres to express their existence.